Effect of immediate dentin sealing and temporary cement removal on bond strength of resin cements to dentin - Guilard, Luís Felipe; Serafini Dapieve, Kiara; Giordani, João Carlos; Susin, Alexandre Henrique; Valandro, Luiz Felipe; Rippe, Marília Pivetta (Brazilian Dental Science, 2022)
Objective: To evaluate the influence of immediate dentin sealing (IDS) and mechanical methods for removing thetemporary cement on the bond strength between dentin and resin cements. Material and Methods: Bovine incisorswere ground until dentin exposure and divided according to two factors: “dentin surface treatment”’ - cleaningwith manual dental excavator (DE), with Robinson bristle brush and pumice paste (PP) or IDS application withSingle Bond 2 (IDS/SB+PP) or Single Bond Universal (IDS/SBU+PP) plus cleaning with PP; and “resin cement”- Self-adhesive (RelyX U200) or conventional cement with self-etching adhesive (Multilink Automix). Simulatingprovisional restoration, acrylic resin plates were cemented onto the dentin surface (with or without IDS) with anon-eugenol temporary cement, and stored in distilled water (37 ºC; 7 days). The acrylic plates were removed, thedentin surface was cleaned (PP or DE), and starch tubes were positioned on the dentin where the resin cementswere applied. After 24 h, the specimens were submitted to a microshear test (wire-loop method). Results: Twowayanalysis of variance showed statistically significant influence of dentine surface treatments (p< 0.001) andresin cement (p= 0.001) in the bond strength values. The IDS/SBU+PP/U200 (7.24 MPa) and IDS/SBU+PP/MULTI (6.40 MPa) groups presented higher values when compared to cleaning with DE (DE/U200= 4.60 MPa;DE/MULTI= 1.45 MPa) and PP (PP/U200= 3.74 MPa; PP/MULTI= 3.14 MPa) Statistical difference was alsofound between the cements when dental excavator treatment was used (RelyX U200 > Multilink Automix). TheIDS/SBU+PP protocol presented a higher percentage of cohesive failures. The micrographs showed differencesin dentin surface characteristics among the groups. Conclusion: Immediate dentin sealing increased the bondstrength of the resin cements to dentin compared to mechanical cleaning only, regardless the resin cement.KEYWORDSCleaning; Dentin sealing; Provisional cement; Resin cement.